Selective decrease of bis(monoacylglycero)phosphate content in macrophages by high supplementation with docosahexaenoic acid - Bouvier, Jérôme; Zemski Berry, Karin A; Hullin-Matsuda, Françoise; Makino, Asami; Michaud, Sabine; Geloën, Alain; Murphy, Robert C; Kobayashi, Toshihide; Lagarde, Michel; Delton-Vandenbroucke, Isabelle (Journal of lipid research, 2009)
Bis(monoacylglycero)phosphate (BMP) is a unique phospholipid (PL) preferentially found in late endosomal membranes, where it forms specialized lipid domains. Recently, using cultured macrophages treated with anti-BMP antibody, we showed that BMP-rich domains are involved in cholesterol homeostasis. We had previously stressed the high propensity of BMP to accumulate docosahexaenoic acid (DHA), compared with other PUFAs. Because phosphatidylglycerol (PG) was reported as a precursor for BMP synthesis in RAW macrophages, we examined the effects of PG supplementation on both FA composition and amount of BMP in this cell line. Supplementation with dioleoyl-PG (18:1/18:1-PG) induced BMP accumulation, together with an increase of oleate proportion. Supplementation with high concentrations of didocosahexaenoyl-PG (22:6/22:6-PG) led to a marked enrichment of DHA in BMP, resulting in the formation of diDHA molecular species. However, the amount of BMP was selectively decreased. Similar effects were observed after supplementation with high concentrations of nonesterified DHA. Addition of vitamin E prevented the decrease of BMP and further increased its DHA content. Supplementation with 22:6/22:6-PG promoted BMP accumulation with an enhanced proportion of 22:6/22:6-BMP. DHA-rich BMP was significantly degraded after cell exposure to oxidant conditions, in contrast to oleic acid-rich BMP, which was not affected. Using a cell-free system, we showed that 22:6/22:6-BMP is highly oxidizable and partially protects cholesterol oxidation, compared with 18:1/18:1-BMP. Our data suggest that high DHA content in BMP led to specific degradation of this PL, possibly through the diDHA molecular species, which is very prone to peroxidation and, as such, a potential antioxidant in its immediate vicinity.